2018
DOI: 10.1001/jama.2018.5690
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prescription Medication Use Among Children and Adolescents—United States, 1999-2014

Abstract: In this study of US children and adolescents based on a nationally representative survey, estimates of prescription medication use showed an overall decrease in use of any medication from 1999-2014. The prevalence of asthma medication, ADHD medication, and contraceptive use increased among certain age groups, whereas use of antibiotics, antihistamines, and upper respiratory combination medications decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 23 publications
3
141
0
3
Order By: Relevance
“…25,26 Our findings were also consistent with declining trends in antibiotic prescribing over the last 20 years, particularly for certain drug classes, including penicillins and cephalosporins. 27,28 Our study also corroborates a recent US antibiotic use study in which it was shown that ∼1/3 of antibiotics dispensed for commercially insured children were either clinically inappropriate or without documented diagnoses, whereas nearly half of all fills were of questionable appropriateness. 29 On the other hand, certain classspecific changes in off-label orders (eg, for antihistamines, psychotropic agents) contrast with overall pediatric prescribing trends reported elsewhere.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…25,26 Our findings were also consistent with declining trends in antibiotic prescribing over the last 20 years, particularly for certain drug classes, including penicillins and cephalosporins. 27,28 Our study also corroborates a recent US antibiotic use study in which it was shown that ∼1/3 of antibiotics dispensed for commercially insured children were either clinically inappropriate or without documented diagnoses, whereas nearly half of all fills were of questionable appropriateness. 29 On the other hand, certain classspecific changes in off-label orders (eg, for antihistamines, psychotropic agents) contrast with overall pediatric prescribing trends reported elsewhere.…”
Section: Discussionsupporting
confidence: 87%
“…29 On the other hand, certain classspecific changes in off-label orders (eg, for antihistamines, psychotropic agents) contrast with overall pediatric prescribing trends reported elsewhere. 28 These discrepancies may relate to our focus on off-label orders as well as differences in data source and exposure definitions; in our study using the NAMCS, we captured physician-reported data on prescribed and recommended OTC drugs, whereas in a study using the National Health and Nutrition Examination Survey, researchers were focused on self-reported data on prescribed (not OTC) drugs taken (not ordered) in the previous month.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was the frequency of prescription of a given drug class. We extracted drug names from prescription text and classified the drugs according to the Multum Lexicon Plus drug database (Appendix Table 1) 13,14 . An additional category was created for fluoride‐based drugs by separating the drugs from the broader class of “Throat and Mouth Preparation.” This was done because of their relevance to oral health and their high usage.…”
Section: Methodsmentioning
confidence: 99%
“…Prescription stimulants such as methylphenidate and nonstimulants such as atomoxetine are labeled for the treatment of attention-deficit/hyperactivity disorder (ADHD) from age approximately 6 and above years, and are also commonly used in medical practice for the management of non-core symptoms of autism spectrum disorder (ASD) [1]. In the USA and in Europe, there has been a trend toward higher prescription rates of these drugs (hereon referred to as "ADHD medications") for both children and adults over the past 2 decades; nevertheless, use remains most common in middle childhood, and not all ADHD diagnosed individuals are prescribed ADHD medications [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%